RESPOND: a patient-centred programme to prevent secondary falls in older people presenting to the emergency department with a fall—protocol for a mixed methods programme evaluation. Issue 2 (12th November 2014) - Morris, R L; Brand, C A; Hill, K D; Ayton, D R; Redfern, J; Nyman, S R; Lowthian, J A; Hill, A M; Etherton-Beer, C D; Flicker, L; Hunter, P C; Barker, A L
Abstract : Background: Programme evaluations conducted alongside randomised controlled trials (RCTs) have potential to enhance understanding of trial outcomes. This paper describes a multi-level programme evaluation to be conducted alongside an RCT of a falls prevention programme (RESPOND). Objectives: (1) To conduct a process evaluation in order to identify the degree of implementation fidelity and associated barriers and facilitators. (2) To evaluate the primary intended impact of the programme: participation in fall prevention strategies and the factors influencing participation. (3) To identify the factors influencing RESPOND RCT outcomes: falls, fall injuries and emergency department (ED) re-presentations. Methods/design: 528 community-dwelling adults aged 60–90 years presenting to two EDs with a fall will be recruited and randomly assigned to the intervention or standard care group. All RESPOND participants and RESPOND clinicians will be included in the evaluation. A mixed methods design will be used and a programme logic model will frame the evaluation. Data will be sourced from interviews, focus groups, questionnaires, clinician case notes, recruitment records, participant-completed calendars, hospital administrative datasets and audio-recordings of intervention contacts. Quantitative data will be analysed via descriptive and inferential statistics and qualitative data will be interpreted using thematic analysis. Discussion: The RESPOND programme evaluation will provide information about contextual and influencing factors related to the RESPOND RCT outcomes. The results will assist researchers, clinicians and policy makers regarding decisions about future falls prevention interventions. Insights gained may be applicable to a range of chronic conditions where similar preventive intervention approaches are indicated. Trial registration number: This programme evaluation is linked to the RESPOND RCT which is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12614000336684).